Predictors of hospital stay and home care services use: A population-based, retrospective cohort study in stage IV gastric cancer. (February 2015) - Mahar, Alyson L; Coburn, Natalie G; Viola, Raymond; Johnson, Ana P
Background: Home care services use has been proposed as a means of reducing costs in palliative care by decreasing hospital stay without impacting quality of clinical care; however, little is known about utilization of these services in the time following a terminal cancer diagnosis. Aim: To examine disease, patient and healthcare system predictors of hospital stay, and home care services use in metastatic gastric cancer patients. Design: This is a population-based, retrospective cohort study. Chart review and administrative data were linked, using a 26-month time horizon to collect health services data. Participants: All patients diagnosed with metastatic gastric cancer in the province of Ontario between 2005 and 2008 were included in the study ( n  = 1433). Results: Age, comorbidity, tumor location, and burden of metastatic disease were identified as predictors of hospital stay and receipt of home care services. Individuals who received home care services spent fewer days in hospital than individuals who did not (relative risk: 0.44; 95% confidence interval: 0.38–0.51). Patients who interacted with a high-volume oncology specialist had shorter cumulative hospital stay (relative risk: 0.62; 95% confidence interval: 0.54–0.71) and were less likely to receive home care services (relative risk: 0.80; 95% confidence interval: 0.72–0.88) than those who did not. Conclusion: Examining how differences in hospital stay and home care services use impact clinical outcomes and how policies may reduce costs to the healthcare system is necessary.